αAsarone alleviates neuronal injury by facilitating autophagy via miR-499-5p/PDCD4/ATG5 signaling pathway in ischemia stroke - Yonghuan Yan; Linfang Wu; Lu Wang; Dandan Wang; Mengting Huang; Jinyong Peng; Jinyong Peng; Yingying Huang; Yingying Huang; Yingying Huang (Frontiers in Pharmacology)
IntroductionαAsarone, an essential oil derived from Acorus gramineus Aiton, which has been successfully used to treat epilepsy in traditional chinese medicine, and has also been reported to confer neuroprotective effects on stroke. However, its mechanism of action remains poorly understood.MethodsThe effects of αAsarone on autophagy were examined by WB, RT-qPCR, immunofluorescence colocalization, transmission electron microscope, and autophagic flux activity was measured by infecting HT22 cells with mRFP-GFP-LC3 adenovirus. And then, cells were transfected with both mimic-miR-499-5p and inhibit-miR-499-5p to investigate the role of miR-499-5p in regulating the effects of αAsarone on stroke. To further clarify the protective effect of αAsarone in vivo, TTC staining, neurological function score, H&E staining, Nissl staining, Laser speckle contrast imaging, transmission electron microscopy, immunofluorescence colocalization, WB and RT-qPCR were performed in the MCAO mice.ResultsαAsarone was observed to inhibit the apoptosis of neuronal cells, and enhance autophagy. In addition, αAsarone promoted the expression of miR-499-5p. Targeting miR-499-5p can negatively regulate PDCD4 expression and the results from the dual-luciferase reporter assay demonstrate the direct targeting of PDCD4 by miR-499-5p. Promoting miR-499-5p can decrease the expression of PDCD4, increase ATG5, and enhance the protective effect of αAsarone on OGD/R injury while inhibiting miR-499-5p can weaken the effect of αAsarone. In vivo experiments further confirmed that αAsarone improved mice MCAO as evidenced by the amelioration of the neurological deficits and facilitated neuronal autophagy. Furthermore, we found that αAsarone reversed the effect of chloroquine, an autophagy inhibitor, and enhanced neuronal autophagy via miR-499-5p/PDCD4/ATG5 signaling pathway.DiscussionOur data suggest that αAsarone alleviates neuronal injury of stroke by facilitating neuronal autophagy through the miR-499-5p/PDCD4/ATG5 signaling pathway.